Review potensi Emblica officinalis (Amla) dalam mengatasi gangguan metabolisme dislipidemia dan antioksidan - Warditiani, Ni Kadek; Sari, Pande Made Nova Armita; Astuti, Ni Made Widi; Wirasuta, I Made Agus Gelgel (Jurnal Farmasi Udayana; Vol. 12, No 1, Tahun 2023DO - 10.24843/JFU.2023.v12.i01.p10, 2023)
Emblica officinalis (Amla) is a plant that is not widely utilized in Bali, but it has tremendous potential. This study aims to investigate the antioxidant and anti-dyslipidemia potential of Amla. Literature search was conducted on Pubmed, Scopus, and Science Direct, followed by screening and review to match the inclusion and exclusion criteria. The search resulted in 346 articles, and after reviewing and screening the titles, keywords, and abstracts, 12 articles that met the criteria were obtained. The review findings indicate that Emblica officinalis (Amla) has a strong potential in preventing or addressing cardiovascular disorders such as atherosclerosis due to its abilities as a potential anti-dyslipidemia and antioxidant agent.